Figure 2 from: Juswara L, Schuiteman A, Droissart V (2016) Four new orchid species from the Lengguru fold belt, West Papua, Indonesia. PhytoKeys 61: 47-59. https://doi.org/10.3897/phytokeys.61.7590 - Juswara, Lina; Schuiteman, Andre; Droissart, Vincent (Zenodo, 2016)
Figure 2 - A Bulbophyllum leucoglossum: 1 flower 2 dorsal sepal 3 lateral sepal 4 petal; 5, lip, adaxial view 6 lip, abaxial view 7 detail of crest on lip 8 column and base of lip; all after Droissart & Juswara 1789; B Dendrobium centrosepalum: 1 flower 2 flower, lateral view 3 floral bract 4 dorsal sepal 5 lateral sepal 6 petal 7 lip 8 flower, cut open 9 column 10 anther 11 pollinia; all after Droissart & Juswara 1736; C Dendrobium taeniocaule: 1 flower 2 dorsal sepal 3 lateral sepal 4 petal 5 lip 6 mentum 7 column, lateral view 8 column, ventral view; all after Droissart & Juswara 1739; D Taeniophyllum pyriforme: 1 flower 2 dorsal sepal 3 lateral sepal 4 petal 5 lip 6 column 7 anther, dorsal view 8 anther, lateral view; all after Droissart & Juswara 1735. Single scale bar = 1 mm; double scale bar = 1 cm. Drawing: Judi Stone.